Selecting sewage sludge treatment alternatives in modern wastewater treatment plants using environmental decision support systems. (16th November 2015) - Garrido-Baserba, M.; Molinos-Senante, M.; Abelleira-Pereira, J.M.; Fdez-Güelfo, L.A.; Poch, M.; Hernández-Sancho, F.
Abstract: The importance of the sewage sludge treatment within the field of wastewater treatment plants (WWTPs) suggests new dimensions of analysis where the relevance of economic criteria combined with the associated environmental issues are increasing the sludge management complexity. For supporting the decision process and for comparative purposes, this study assesses five alternative configurations for sludge treatment, namely: mesophilic and termophilic anaerobic digestion plus composting, incineration, gasification, and supercritical water oxidation (SCWO). The global warming potential (GWP) and the annual cash flow of each alternative are used to estimate a composite indicator for each alternative. Stakeholders' preferences are integrated into the assessment through the development of five scenarios prioritizing economic or environmental aspects. A case study for a 1 million person equivalent WWTP proved that SCWO is the most adequate option if economic and environmental criteria are considered equally important. However, if the economic assessment is prioritized over the environmental one, thermophilic anaerobic digestion followed by composting turned out to be the most appropriate option. The proposed approach contributes to the implementation of more suitable sewage sludge treatment lines since it provides an indicator for each alternative embracing economic and GWP issues. Highlights: NovEDAR_EDSS software was applied to explore sewage sludge treatment. Sludge treatment alternatives were identified and evaluated. Integration of economic and environmental criteria into a single composite indicator. Supporting sewage sludge treatment decisions by engineers and stakeholders.